Analisis Implementasi Anggaran Berbasis Kinerja pada Organisasi Perangkat Daerah: Pendekatan Kualitatif - Muhamad syahwildan; Ade Syahrozi; Padly Nahampun; Lutvia Nida; Edwin Najib Hidayat (CV. ITTC INDONESIA, 2025)
This study aims to analyze the implementation of performance-based budgeting in local government agencies (Organisasi Perangkat Daerah/OPD). In the context of bureaucratic reform and the increasing demand for public transparency and accountability, performance-based budgeting serves as a strategic instrument to improve the efficiency and effectiveness of public financial management. Using a qualitative descriptive approach based on literature review, this research explores various challenges and obstacles that hinder the optimal implementation of this budgeting model. The results show that many OPDs still face limitations in understanding performance concepts, lack integrated information systems, and are constrained by inadequate human resource capacity. Evaluation processes also tend to focus on budget absorption rather than outcomes, and organizational commitment to results-based management remains weak. To address these issues, the study recommends strengthening technical competencies, integrating planning and budgeting systems, improving performance-based evaluations, and fostering a culture of accountability within public institutions. This research contributes to the discourse on public budgeting reforms by offering insights into how performance orientation in budgeting can be institutionalized more effectively at the regional government level.